A study on the correlation between knowledge and practice of correct working posture among UPCD batch 96 clinicians - Sanchez, Rowena
A significant number of clinicians and even dentists often complain of pain in the neck and the low back and this particular hazard has even caused a number of dentists to discontinue their practice. This study aims to determine the relation between the level of knowledge on proper working posture and the maintenance of this posture in clinical practice. Two different sets of questionnaires were given out to the Junior clinicians to ascertain the level of their knowledge and to determine their posture habits. Results were subjected to the test for independence and proportion (0.05 level of significance). The data gathered reveal that 92.8% of the Junior clinicians have sufficient knowledge on proper posture but only 10.7% apply this sufficient knowledge in clinical practice. We therefore conclude that there Is no relation between the sufficiency of knowledge on proper working posture and the maintenance of this posture in clinical practice.